Effects of HarmoKnee Injury Prevention Training Program on Knee Isometric Strength of Young Professional Male Soccer Players - Mostafa Shojaei; Abdolhamid Daneshjoo; Nader Rahnama (Vesnu Publications, 2011)
Introduction: Based on the crucial role of muscle strength in performance and injury prevention, insufficient muscle strength has been implicated in injuries to soccer players' lower limbs. This study investigated the effects of an injury prevention training program on knee isometric strength of young professional male soccer players. Materials and Methods: Twenty-four young professional soccer players with at least five years of experience in playing soccer professionally on a regular schedule were divided into two groups: experimental group (12 players) and control group (12 players). Participants in experimental group underwent a knee preventive intervention program (called "HarmoKnee program") three times per week for eight successive weeks. A Biodex Isokinetic Dynamometer used to study the hamstring and quadriceps strength at 30˚, 60˚ and 90˚ knee angles. Paired t-test, independent sample t-test and two way repeated measures were used for statistical analysis of data (P < 0.05). Results: The results of this study showed that in experimental group, quadriceps peak torque (PT) increased significantly at 60˚ and 90˚ (P < 0.05). Significant differences were found between hamstring's PT at 30˚ and 60˚ in the experimental group (P < 0.05). Quadriceps muscles PT of the experimental group were significantly different at different angles (P = 0.000). For all cases, quadriceps PT was highest at 90˚ (292.1 Nm). For the hamstring muscle's PT, significant differences were found among three angles in the experimental group (P = 0.000). The most hamstring PT was revealed in 30˚ of the knee joint (155.1 Nm). Conclusion: It is concluded that the HarmoKnee prevention program is a useful program for improving knee muscle strength in young male professional soccer players. Data from this research can help trainers to decide whether players need physical therapy to improve their balance and strength and also are helpful in designing injury prevention programs for young professional soccer players. Keywords: Professional soccer player, Hamstrings, Quadriceps, Isometric